The effect of special exercises using the (Blazepod) device to develop defense against shooting among advanced basketball players - Diaa, Mohamed; Jaro , Shirzad (Journal of Physical Education, 2025)
The purpose of this paper is to prepare special exercises for the kinetic response using the (Blazepod) device for advanced basketball players and to identify the effect of using the (Blazepod) device in developing defense against shooting among advanced basketball players. The researchers used the experimental method in the manner of two equal groups (experimental and control) with two pre and post-tests for its suitability and the nature of the problem to be solved. The sample was chosen by the intentional method, which consisted of (24) players from (Al-Adhamiya and Al-Tijara clubs) of advanced players, due to the availability of the sample and the ease of controlling it, and being one of the players participating in the Iraqi league for the first degree, since the sample is committed to daily training, as well as the availability of the hall and tools, and the sample was divided into two groups, one experimental, represented in the Al-Adhamiya Sports Club, the number of which is (12) players, and the other is a control group represented by Al-Tijara Sports Club, numbering (12) players. The experimental group applied the exercises of speed of kinetic response and defense movements prepared by the researcher on the device, and the control group applied the trainer’s free exercises without a device. The two researchers conducted homogenization of the sample by extracting the torsion coefficient. One of the most important conclusions reached by the researchers is that the effect of the particular exercises prepared by the researcher using the (Blazepod) training device in developing the endurance of defensive performance significantly among the advanced basketball players (experimental group), and this is evident from the difference between the arithmetic mean between the pre and post-tests, and the effect of the exercises prepared by the coach in developing the endurance of the defensive performance was simple among the advanced basketball players (control group), and this is evident from the difference of the arithmetic mean between the pre and post-tests.